Impact of Indonesia's ICT Development on Economic Growth - Hindrayani, Aniek; Rina, Lelahester; Naufalin, Lina Rifda (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2024)
This study examined the influence of Indonesia's information and communication technology (ICT) development on the country's economic growth both in the short term and long term using a systematic literature review methodology. Systematic searches in several databases (Springer, Scopus, Science Gate, Science Direct, Sinta, Routledge Francis & Taylor, and other International Conferences). The included papers are 24 peer-reviewed studies. Results showed a positive impact of ICT development in Indonesia on economic growth both in the short-run and long-run periods. The impact is also indicated by total factor productivity, human capital resources, and capital per worker. However, there's an inequality of income found in Indonesia regarding the development of ICT.